Insights from the Gender Up Workshop: A Gender Responsive Method to Scale - Souissi, Asma; Ouerghemmi, Hassen; Majri, Rihab; Shiri, Zahra; Dhehibi, Boubaker; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2024)
This report aims to highlight discussions from the Gender-Up workshop on implementing the Controlled Designation of Origin (AOC) for olive oil in the El Kef region. Key stakeholders, including local farmers and government representatives, collaborated to ensure inclusive scaling that addresses the needs of marginalized groups. Using the Gender-Up method, participants defined scaling ambitions and examined social dimensions affecting access to AOC benefits, focusing on challenges faced by vulnerable groups like women and young farmers. The workshop concluded with actionable strategies to promote community engagement and equitable distribution of benefits within the olive oil sector.